Mengungkap Akuntansi Rumah Tangga dalam Keluarga Sentana Desa Pakraman Kaba-Kaba - Widiantari, Putu Wahyu; Atmadja, Anantawikrama Tungga (Vokasi : Jurnal Riset Akuntansi, 2021)
Within households, accounting views and practices vary widely. The purpose of the article is to find out the viewpoint and activities of household bookkeeping carried out in the sentana family of Pakraman Kaba-Kaba Village. This study used a qualitative method with the selection of informants by purposive sampling. Data obtained through observation, interviews, and documentation. The results of the study found the viewpoint and forms of accounting practices carried out by the Sentana family were varied and flexible. This is because the notion of household accounting is not suitable to be applied in the family. There are four household accounting activities, namely budgeting, recording, decision making and long-term financial planning. Within the Sentana family, accounting practices in the form of decision-making are based on mental accounting. The focus of family accounting activities is on the income earned. So that unexpected income gain is used for future plans.